Neurological Prognostication of Cardiac Arrest in an Era of Extracorporeal Membrane Oxygenation. (January 2017) - Sahai, Supreet K.; Majic, Tamara; Patel, Jignesh; Nurok, Michael; Moheet, Asma M.; Rosengart, Axel J.; Lahiri, Shouri
A neuron-specific enolase level greater than 33 ng/mL at days 1 to 3 or status myoclonus within 1 day are traditional indicators of poor neurological prognosis in survivors of cardiac arrest. We report the case of a 70-year-old man who received extracorporeal membrane oxygenation following cardiac arrest. Despite having both an elevated neuron-specific enolase concentration of 68 ng/mL and status myoclonus, he made an excellent neurological recovery. The value of traditional markers of poor prognosis such as elevated neuron-specific enolase or status myoclonus has not been systematically validated in patients treated with extracorporeal membrane oxygenation or therapeutic hypothermia. Straightforward application of practice guidelines in these cases may result in tragic outcomes. This case underscores the need for reliable prognostic markers that account for recent advances in cardiopulmonary and neurological therapies.